Minority Stages Sino-Indonesian Performance and Public Display - Stenberg, Josh (University of Hawaii Press, 2019)
Minority Stages: Sino-Indonesian Performance and Public Display offers intriguing new perspectives on historical and contemporary Sino-Indonesian performance. For the first time in a major study, this community's diverse performance practices are brought together as a family of genres. Combining fieldwork with evidence from Indonesian, Chinese, and Dutch primary and secondary sources, Josh Stenberg takes a close look at Chinese Indonesian self-representation, covering genres from the Dutch colonial period to the present day. From glove puppets of Chinese origin in East Java and Hakka religious processions in West Kalimantan, to wartime political theatre on Sumatra and contemporary Sino-Sundanese choirs and dance groups in Bandung, this book takes readers on a tour of hybrid and diverse expressions of identity, tracing the stories and strategies of minority self-representation over time.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Aug 2019)
Keywords: Geschichte; PERFORMING ARTS / Theater / History & Criticism; Chinesen; Darstellende Kunst; Kultur; Indonesien